The Real Exchange Rate and Employment in China - Dao, Mai.; Chen, Ruo. (Washington, D.C. : International Monetary Fund, 2011)
We examine the impact of real exchange rate fluctuations on sectoral and regional employment in China from 1980 to 2008. In contrast to theoretical predictions, employment in both the tradable and non-tradable sectors contracts following a real appreciation. Our results are robust across different sub-samples, levels of sectoral disaggregation, and are more pronounced for regions with higher export exposure. We attribute our findings to the importance of services as intermediate input in exportable production. We test this channel of exchange rate transmission using regional input-output tables linked with employment data at the region-sector level. The results of this paper have important implications for China's labor market adjustment should the Chinese RMB strengthen in the future. To mitigate the costs of short-run labor market adjustment, appropriate demand management and structural reforms in the non-traded sectors should play an important role.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet